THE CORRELATION BETWEEN STUDENTS’ ARTIFICIAL INTELLIGENCE AND THEIR ENGLISH READING SKILLS ACHIEVEMENT - Lestari, Sri; Usadiati, Wahyuningsih; Misrita, Misrita (ppjbsip, 2021)
Artificial intelligence is intelligence that is added to a system that can be regulated in a scientific context or it can be called artificial intelligence. Students usually use the media to improve their English skills with a variety of mobile applications in mastering effective and critical English in order to gain a better understanding of English reading skills. The aims of this study are to know the correlation between students’ artificial intelligence and their English reading skills achievement in the second semester class of the English Study Program at the Islamic University of Kalimantan, Muhammad Arsyad Al Banjari Banjarmasin. In this research, the researcher uses quantitative approach by correlation technique. To measure students' artificial intelligence, the author shares several questions related to the topic by using google form. The study population is a total of 30 students consists of male and female students in a class. After doing research, it was found that the correlation between students’ artificial intelligence and English reading skill achievement was quite high. This is indicated by the results of the research (0.67), where this value shows that there is a significant relationship between the variable x (students' artificial intelligence) and the variable y (learning outcomes of students' Reading achievement). As for the results showing that the mobile application helps improve students' reading skills in English.AbstrakKecerdasan buatan adalah kecerdasan yang ditambahkan pada suatu sistem yang dapat diatur dalam konteks ilmiah atau bisa disebut kecerdasan buatan. Siswa biasanya menggunakan media untuk meningkatkan kemampuan bahasa Inggris mereka dengan berbagai aplikasi seluler dalam menguasai bahasa Inggris yang efektif dan kritis untuk mendapatkan pemahaman yang lebih baik tentang keterampilan membaca bahasa Inggris. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kecerdasan buatan mahasiswa dengan pencapaian kemampuan membaca bahasa Inggris pada semester dua Program Studi Bahasa Inggris di Universitas Islam Kalimantan, Muhammad Arsyad Al Banjari Banjarmasin. Dalam penelitian ini, peneliti menggunakan pendekatan kuantitatif dengan teknik korelasional. Untuk mengukur kecerdasan buatan siswa, penulis membagikan beberapa pertanyaan terkait topik dengan menggunakan google form. Populasi penelitian ini berjumlah 30 mahasiswa yang terdiri dari laki-laki dan perempuan dalam satu kelas. Setelah dilakukan penelitian, ditemukan bahwa hubungan antara kecerdasan buatan siswa dengan pencapaian keterampilan membaca bahasa Inggris cukup tinggi. Hal ini ditunjukkan oleh hasil penelitian (0,67), dimana nilai ini menunjukkan bahwa terdapat hubungan yang signifikan antara variabel x (kecerdasan buatan siswa) dan variabel y (hasil belajar terhadap prestasi membaca siswa). Adapun hasil yang menunjukkan bahwa aplikasi mobile membantu meningkatkan kemampuan membaca siswa dalam bahasa Inggris.